SIGNAL REACTION OF MICRO AND MACRO VARIABLE TO COMPANY STOCK RETURN - Endah Sri Rahmawati; Faizah Syihab (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
This study aims to find out the effect of variable micro and macro variables of companies with linkages signaling theory on stock returns. This study uses panel data models. This study focused company Basic and Chemical Industry sector listed in Indonesia Stock Exchange 2011-2017 period, in which the selection of samples in this study using purposive sampling method as many as 21 companies. The results of this study showed R2 value of 60.09%. The results of this study showed that variables Trade Volume Stocks (VPS), Volatility of Stock Price (VPS), Company Size (SF), Profitability (PROF), Solvency (SOLV), Inflation (CPI), and Exchange Rate (EXCRATE) simultaneously influence Company Stock Return. There are three variables that partial effect on stock returns is Stock Price Volatility (VPS), Profitability (PROF), and Inflation (CPI). Based on these results, the company is advised to observe micro and macro variables that have relevance to the ongoing investment in capital market activities, as it will directly impact on the interest of market participants (investors). Companies that are considered to have good performance will certainly give a good signal in the capital market, so it will attract investors to carry out investment activities which will then increase stock returns.